Influence of calcium nutrition on anthracnose of bean - Muniz, Maria de Fátima Silva; Muchovej, James John; Muchovej, Rosa Maria Castro; Venegas, Victor Hugo Alvarez; Brommonschenkel, Sérgio Herminio; Maffia, Luiz Antônio (Pesquisa Agropecuaria Brasileira, 1991)
The influence of calcium present in hydroponic solution on the severity of anthracnose of bean was studied under growth chamber conditions. Plants of the cultivars Jalo (susceptible) and Ouro (resistant) grown in hydroponic solutions containing 9 doses of calcium (0.1; 0.2; 0.3; 0.4; 0.5; 1.0; 2.0; 3.0 and 4.0 mN) were inoculated at 10 days of age with 2 x 106 conidia/ml using an isolate of Colletotrichum lindemuthianum race alpha. Plants grown in 0.1 and 0.2 mN Ca showed symptoms of calcium deficiency. Twelve days after inoculation, disease severity was evaluated. The aerial parts of the plants were then harvested, dried and analysied for levels of Ca, Mg, K, P, Zn, Cu, Mn and Fe. Results indicated that resistance of the cultivars to anthracnose was not due to the level of Ca present in the tissue.